Long-term reproducible expression in human fetal liver hematopoietic stem cells with a UCOE-based lentiviral vector - Dighe, Niraja (2014)
Hematopoietic Stem Cell (HSC) targeted gene transfer is an attractive treatment option for a number of hematopoietic disorders caused by single gene defects. However, extensive methylation of promoter sequences results in silencing of therapeutic gene expression. The choice of an appropriate promoter is therefore crucial for reproducible, stable and long-term transgene expression in clinical gene therapy. Recent studies suggest efficient and stable expression of transgenes from the ubiquitous chromatin opening element (UCOE) derived from the human HNRPA2B1-CBX3 locus can be achieved in murine HSC. Here, we compared the use of HNRPA2B1-CBX3 UCOE (A2UCOE)-mediated transgene regulation to two other frequently used promoters namely EF1α and PGK in human fetal liver-derived HSC (hflHSC). Efficient transduction of hflHSC with a lentiviral vector containing an HNRPA2B1-CBX3 UCOE-eGFP (A2UCOE-eGFP) cassette was achieved at higher levels than that obtained with umbilical cord blood derived HSC (3.1x; p<0.001). While hflHSC were readily transduced with all three test vectors (A2UCOE-eGFP, PGK-eGFP and EF1α-eGFP), only the A2-UCOE construct demonstrated sustained transgene expression in vitro over 24 days (p<0.001). In contrast, within 10 days in culture a rapid decline in transgene expression in both PGK-eGFP and EF1α-eGFP transduced hflHSC was seen. Subsequently, injection of transduced cells into immunodeficient mice (NOD/SCID/Il2rg-/-) demonstrated sustained eGFP expression for the A2UCOE-eGFP group up to 10 months post transplantation whereas PGK-eGFP and EF1α-eGFP transduced hflHSC showed a 5.1 and 22.2 fold reduction respectively over the same time period. We conclude that the A2UCOE allows a more efficient and stable expression in hflHSC to be achieved than either the PGK or EF1α promoters and at lower vector copy number per cell.